Do not forget asthma comorbidities in pediatric severe asthma! - Ronco, Lucia; Folino, Anna; Goia, Manuela; Crida, Benedetta; Esposito, Irene; Bignamini, Elisabetta (Frontiers in Pediatrics, 2022)
Asthma is the most common chronic respiratory disease in childhood. The long-term goals in managing asthma aim to control symptoms and prevent exacerbations, as well as to reduce side effects of therapy and mortality disease-related. Most of patients have mild to moderate asthma and respond well to standard therapies. However, a minor proportion of children with asthma has severe disease that remains uncontrolled despite optimal adherence to prescribed therapy and treatment of contributory factors, including trigger exposures and comorbidities, which can mimic or worsen asthma and contribute to exacerbations and poor quality of life. Evaluation of comorbidities is fundamental to optimize the management of the disease in a subgroup of patients with poor responder asthma. The overall aim of this article is to describe characteristics of main pediatric severe asthma comorbidities reported in literature, giving clinicians tools to recognize and manage properly these conditions.di